Educational Research in Latin America: A Response to Akkary and Pérez - Narodowski, Mariano (Education Policy Analysis Archives, 1999)
In a recent article which appeared in Educational Policy Analysis Archives 6 (7) 1998, "Educational Research in Latin America: Review and Perspectives," Abdeljalil Akkari and Soledad Pérez envisage carrying out a general analysis of the situation of educational research in Latin America, in an attempt to describe the context of its historical formation. They focus on the main theoretical framework, they identify the principal institutions involved in educational research, and consider the priorities for future research in the region.